السياسة الخارجية التركية تجاه المتغيرات الامنية في العراق بعد عام 2003 - حسن, المشرف: أ.م.د. كمال عبدالله; جلال, طالبة ماجستير: جرا شمال (Sulaimani Journal for Humanities, 2023)
The Justice and Development Party's victory in the elections and the formation of the government in 2002, constituted a key factor in changing Turkey's policy of openness towards its geographical and historical depth. Iraq is considered a gateway to the Middle East and constitutes a vital area for the security of its national interests. Therefore, the Turkish foreign policy sought to exercise its role in Iraq, with a new approach aimed at adapting to the variables of the regional and international reality, which were reflected in the Middle East region. After the developments that followed the events of September 11, 2001, the US occupation of Iraq in 2003, the events of the Arab countries in 2011, and Iran's attempt to emerge as a nuclear power, all these variables imposed on Turkey to reshape its foreign policy in accordance with regional and international developments, which expressed the new geological challenges. Turkey implemented its foreign policy with the aim of establishing a new regional order, to address the political and security vacuum in light of the escalation of terrorism after 2014, in accordance with the new Turkish policy to serve its security and national interests.